ANALISIS STRATEGI PROMOSI PRODUK EMAZO MERAH DALAM MENINGKATKAN VOLUME PENJUALAN (Analysis of Emazo Red Product Promotion Strategies in Increasing Sales Volume) - Maysya Adetia; Fatchur Rozci (Study Program of Agribusiness, Faculty of Agriculture, University of Wijaya Kusuma Surabay, 2024)
Emazo Merah is an insecticide product from PT. Petrosida Gresik which has been updated to be more effective in eradicating sundep and bedlet pests, especially in vulnerable areas such as Gresik and Lamongan Regencies. Promotion through demonstration plots/demspay is needed so that rice farmers can see firsthand the advantages of this product, taking into account land and weather conditions. This study uses observations and interviews with 5 promotion organizers to analyze areas with high sales potential. The results of the analysis show that the promotion of Emazo Merah in Gresik and Lamongan has a total IFAS matrix score of 2.95 and EFAS of 1.83, which places it in quadrant III. To increase sales, it is recommended to conduct market research, display testimonials or direct product trials, and take advantage of good relationships with consumers, kiosks, and agricultural offices.Keywords: Emazo Merah, Pesticide, Promotion, Market Research.